1998
DOI: 10.1002/(sici)1098-2337(1998)24:3<161::aid-ab1>3.0.co;2-o
|View full text |Cite
|
Sign up to set email alerts
|

The interactive relations between trait hostility, pain, and aggressive thoughts

Abstract: A recent model of affective aggression [Anderson et al., 1996] proposes that individual differences and situational factors can affect aggressive behavior through cognitive, affective, and arousal pathways. An experiment tested the relations of trait hostility and physical pain to aggressive thoughts (the cognitive path) and state hostility (the affective path). The experiment found an interaction between pain and trait hostility on aggressive thoughts. Trait hostile participants who experienced pain rated amb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
70
0

Year Published

2000
2000
2014
2014

Publication Types

Select...
5
5

Relationship

4
6

Authors

Journals

citations
Cited by 77 publications
(73 citation statements)
references
References 35 publications
3
70
0
Order By: Relevance
“…Our theoretical approach is the GAAM, which has emerged from our work on a variety of aggression-related domains (Anderson, Anderson, & Deuser, 1996;Anderson, Deuser, & DeNeve, 1995;Anderson, Anderson, Dill, & Deuser, 1998;Dill, Anderson, Anderson, & Deuser, 1997;Lindsay & Anderson, in press). The model integrates existing theory and data concerning the learning, development, instigation, and expression of human aggression.…”
Section: Gaam: Overviewmentioning
confidence: 99%
“…Our theoretical approach is the GAAM, which has emerged from our work on a variety of aggression-related domains (Anderson, Anderson, & Deuser, 1996;Anderson, Deuser, & DeNeve, 1995;Anderson, Anderson, Dill, & Deuser, 1998;Dill, Anderson, Anderson, & Deuser, 1997;Lindsay & Anderson, in press). The model integrates existing theory and data concerning the learning, development, instigation, and expression of human aggression.…”
Section: Gaam: Overviewmentioning
confidence: 99%
“…Even with these possibilities, however, laboratory experiments in which physical discomfort or pain was deliberately established have shown that the decidedly unpleasant physical sensations in themselves can be angering and lead to affective aggression (e.g., C. A. Anderson, Deuser, & DeNeve, 1995;K. B. Anderson, Anderson, Dill, & Deuser, 1998; see also Berkowitz, 1993aBerkowitz, , 1993bBerkowitz, , 2003, perhaps particularly in people especially disposed to negative emotionality (Verona, Patrick, & Lang, 2002).…”
Section: Must There Be An External Cause Of the Negative Event?mentioning
confidence: 99%
“…Aggressiveness is a complex phenomenon and can be a correlate of other underlying disorders such as depression and pain (13,14). As previous studies have reported significant psychiatric symptoms in patients with CH (4,(15)(16)(17), higher levels of aggression -if present -could be explained by this concomitant spectrum of disease.…”
Section: Introductionmentioning
confidence: 99%